End-of-life stories : crossing disciplinary boundaries - Gelfand, Donald E. (Death and suicide series., 2005)
End-of-life experiences are often viewed in terms of only one perspective such as medicine. In this volume, a variety of end-of life experiences are presented and each case is analyzed from a variety of disciplinary perspectives. These range across a broad array of the helping professions, and disciplines such as information, law and the social sciences. The book provides a variety of narratives about end-of-life experiences contributed by members of the Wayne State University End-of-Life Interdisciplinary Project. Each of the narratives is then analyzed from several different disciplinary per.